Słownik uniwersytecki niemiecko-polski jako wsparcie mobilności studentów - Mikucka, Martyna; Krajka, Sławomir (Investigationes Linguisticae, 2010)
This article presents the results obtained by translating UNILEX Universitätswörterbuch für in- und ausländische Studierende by Prof. Burkhard Schaeder und Aleka Rapti from German into Polish by the Student Translator Association at the Institute of Applied Linguistics in Adam Mickiewicz University in Poznań. In the period of growing mobility among polish students who nowadays have great opportunities to study abroad, one of the most significant aspects of the student exchange is the ability to speak foreign languages. There are plenty of dictionaries, glossaries or guides available that can be helpful in helping students to get used to the education system in foreign universities, but they miss out important facts or not up-todate in most cases. Because of this fact the members of the Student Translator Association have come to the conclusion that translating the Unilex from German into Polish could become an advantage for polish students studying in Germany for a certain period of time.